2021
DOI: 10.1186/s13019-021-01418-w
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transluminal stenting for superior vena cava syndrome caused by malignant tumors: a single-center retrospective study

Abstract: Objectives To evaluate the efficacy of percutaneous stent placement in the treatment of superior vena cava syndrome caused by malignant tumors. Methods We retrospectively analyzed the clinical data of 32 patients with superior vena cava syndrome who underwent percutaneous endovascular stent treatment in our department from 2015 to 2019 due to malignant tumors and summarized the patient’s sex, age, tumor type, endovascular treatment plan, complicati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Radiotherapy, chemotherapy with anticancer drugs, and single or combined surgical therapy are usually selected [2,5,6]. Liu H, et al [7] reported that, for SVCS caused by malignant tumors, percutaneous endoluminal stent therapy could quickly and effectively relieve the clinical symptoms of patients, and the incidence…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy, chemotherapy with anticancer drugs, and single or combined surgical therapy are usually selected [2,5,6]. Liu H, et al [7] reported that, for SVCS caused by malignant tumors, percutaneous endoluminal stent therapy could quickly and effectively relieve the clinical symptoms of patients, and the incidence…”
Section: Discussionmentioning
confidence: 99%